Diagnóstico de las estrategias de comunicación del departamento riesgos laborales, salud ocupacional y gestión ambiental para la prevención de emergencias y desastres en la universidad nacional de Chimborazo durante el periodo junio-diciembre 2016 - Pilco Cayambe, Jonny Alejandro (2018)
The purpose of this research is to diagnose the communication strategies of the Occupational Health, Occupational Health and Environmental Management Department for the prevention of emergencies and disasters at the National University of Chimborazo, using techniques and instruments for gathering information such as: surveys, interviews, questionnaire sources, which will allow teachers, employees and workers a timely response to an emergency or disaster. Our starting point is communication where we will define the importance and how communication networks influence in the face of an emergency or disaster, and then identify the communication strategies of the Occupational Risk, Occupational Health and Environmental Management Department for the prevention of emergencies and disasters in the National University of Chimborazo. Once the analysis of the communication strategies was done, the level of efficiency of the strategies in the prevention of emergencies and disasters was determined, for which observations were made of eventualities that have appeared in the National University of Chimborazo during the June- December 2016.